A Time(s), space(s) and communication in Castells’s ‘Network Society’* - Bert Olivier (Communicare)
In ‘The Rise of the Network Society’ (2010), Manuel Castells elaborates on what today is common knowledge, namely the notion of a society that is characterised both by networks of electronically mediated communication and by networks undergirding economic exchanges worldwide. In this article, I explore a dissonance issuing from a feature of the network society, namely what Castells calls the ‘transformation of space and time in the human experience’. In this context, he distinguishes between ‘the space of places’ and ‘the space of flows’, with the former referring to the historically familiar sense of space as a material precondition of social interaction and of architectural modulation into ‘place’, and the latter to a novel form of spatiality, one that is related to social interaction that has been fundamentally modified by advanced communication technologies and is characterised by simultaneity, regardless of physical distance. This, in turn, is related to what Castells labels ‘timeless time’, which is noticeable where customary time sequences are blurred in certain contemporary practices, such as virtually instantaneous financial transactions, ‘instant wars’ and virtual communication. This contrasts with both ordinary, ‘human’ time and also with evolutionary ‘glacial time’ – a notion operative in the ecological movement and one that increasingly clashes with the demands of ‘timeless time’ in the network society. The article reconstructs Castells’s comprehensive vision and points to the relevance of the conflict between these respective notions of space and time for contemporary communication practices. It also engages critically with the social implications of the dominant modes of space and time.